Developing and Validating an Assessment Instrument for Organizational Performances of Construction Organization - Khairul Firdaus, Anuar; Nurhaizan, Mohd Zainudin; Muhammad Ashraf, Fauzi (Akademia Baru, 2024)
Evaluating the performance of construction organizations is important for ensuring the success of construction projects-based nature. However, there are no standardized instruments and a single way to measure how well construction organizations perform, making it difficult for researchers and practitioners to get an accurate picture of their performance. This study aims to develop and validate an instrument for assessing organizational performances of construction organizations. The instrument was reviewed by an eight (8) panel of experts, who rated the items on their relevance (essential) to the construct of organizational performance. The Content Validity Ratio (CVR) results showed that 21 of 59 items were considered the most critical by the content experts, and the results for Item Level Content Validity Index (I-CVI) showed that 46 items were considered appropriate. These results showed that the instrument has adequate content validity. The outcomes of this study have important implications for the use of this instrument in organizational performance assessment for the construction industry. The instrument can be used to measure construction organizational performance in a comprehensive and systematic way. This will help researchers and practitioners to better understand the factors that contribute to construction organizational performance and to develop interventions to improve this construct.